Pelaksanaan Kebijakan DAK Non Fisik Bidang Kesehatan untuk Tenaga Kontrak Promosi Kesehatan di Kabupaten Sumbawa dan Kabupaten Sleman Tahun 2016 - Yuniati Yuniati; Laksono Trisnantoro; Dwi Handono Sulistyo (Center for Health Policy and Management, 2017)
ABSTRACTBackground : In order to support the global commitment in addressing the burden of non-communicable diseases, the government through the Ministry of Health set the one of the targets of the National Development Strategy Plan is the promotion and preventive service through the availability of health promotion personnel at the Puskesmas. To meet these needs the government issued a policy that is the Regulation of the Minister of Health No. 82 of 2015 on Technical Guidance Special Allocation Fund for Health Operational Support where one of financing is for promotive and preventive activities directed to finance one (1) contract health promotion workers. Aims : To analyze the implementation of the policy of Non-Physical Special Allocation Fund of 2016 to recruit Health Promotion Contract Workers for Puskesmas in Sumbawa and Sleman districts. Methods : A single case study study was established using Implementation Research carried out at the Health Office in Sumbawa and Sleman districts. Informants were interviewed using the Consolidated for Implementation Research (CFIR) framework as a guide in collecting and analyzing qualitative data. Result :The most dominant factor of CFIRs affecting the implementation of contract labor policies is the internal communication network, particularly the involvement of the management. Organizational needs are the reasons for implementing a policy, but this is not a major factor in the implementation of a policy. Meeting the needs of the organization is influenced by the involvement factor of the leader of the organization in this case the leadership commitment to the vision of the organization, the implementation is also influenced by the external communication network organization that is: advocacy, coordination and cooperation with cross-related sector. Conclusion : The policy of recruitment of contract workers in Sleman district was successfully implemented because the policy makers and implementers played a good role, while Sumbawa regency did not implement this policy because of the difference perception about the need of health promotion personnel between Puskesmas as implementer of policy and health department as policy maker which supervises the Puskesmas. Keyword : Implementation, outcome, DAK non-Physical policy, Contract force health promotion, Consolidated Framework for Implementation ResearchABSTRAKLatar belakang: Isu global tentang beban penyakit tidak menular menjadi salah satu dasar kebijakan nasional di bidang kesehatan. Penyakit tidak menular adalah penyebab 68% kematian di dunia dan sebagian terjadi pada negara berpenghasilan menengah ke bawah. Dalam rangka mendukung komitmen global pemerintah melalui Kementerian Kesehatan menetapkan salah satu sasaran Rencana Strategi Pembangunan Nasional (RPJMN) adalah upaya pelayanan promotif dan preventif dalam rangka menurunkan kejadian penyakit tidak menular yang dalam beberapa tahun terakhir berkembang pesat. Untuk memenuhi kebutuhan tersebut pemerintah melalui Kementerian Kesehatan mengeluarkan kebijakan yaitu Peraturan Menteri Kesehatan Nomor 82 Tahun 2015 tentang Juknis Dana Alokasi Khusus sebagai Bantuan Operasional Kesehatan dimana salah satu pembiayaannya adalah untuk kegiatan promotif dan preventif yang diarahkan untuk membiayai satu (1) orang tenaga kontrak promosi kesehatan. Tujuan untuk menganalisis pelaksanaan kebijakan Dana Alokasi Khusus Non Fisik Tahun 2016 untuk merekrut Tenaga Kontrak Promosi Kesehatan di Kabupaten Sumbawa dan Kabupaten Sleman Metode: Penelitian studi kasus tunggal terjalin dengan strategi pendekatan menggunakan Riset Implementasi ini dilakukan di Dinas Kesehatan di Kabupaten Sumbawa yang belum melaksanakan kebijakan Tenaga Kontrak Promosi Kesehatan dan Kabupaten Sleman yang telah melaksanakanya. Informan diwawancarai dengan menggunakan kerangka kerja The Consolidated for Implementation Research (CFIR) sebagai panduan dalam pengumpulan dan analisis data kualitatif. Partisipasi aktif pembuat keputusan kebijakan baik di Pusat maupun di Daerah ikut dilibatkan selama proses penelitian berlangsung, mulai dari penentuan topik, pertanyaan penelitian sampai pada pelaksanaan penelitian. Kata kunci: Implementasi, outcome, kebijakan DAK non Fisik, Tenaga Kontrak promosi kesehatan,Consolidated Framework for Implementation Research